Prognostic significance of neutrophil-lymphocyte ratio in hepatocellular carcinoma: a meta-analysis - Xiao, Wei-Kai (BioMed Central, 2014)
BACKGROUNDS: Neutrophil-lymphocyte ratio (NLR) has recently been reported as a predictor of Hepatocellular carcinoma (HCC). However, its prognostic value in HCC still remains controversial. In this study, we aimed to evaluate the association between NLR and clinical outcome of HCC patients by performing meta-analysis. METHODS: A comprehensive literature search for relevant studies published up to August 2013 was performed by using PubMed, Ovid, the Cochrane Library and Web of Science databases. Meta-analysis was performed using hazard ratio (HR) or odds ratio (OR) and 95% confidence intervals (95% CIs) as effect measures. RESULTS: A total of 15 studies encompassing 3094 patients were included in this meta-analysis. Our pooled results showed that high NLR was associated with poor overall survival (OS) and disease free survival (DFS) in HCC initially treated by liver transplantation (HR = 3.42, 95% CI:2.41-4.85,P = 0.000; HR = 5.90, 95% CI:3.99-8.70,P = 0.000, respectively) and surgical resection (HR = 3.33, 95% CI:2.23-4.98, P = 0.000; HR = 2.10, 95% CI: 2.06–2.14, respectively). High NLR was also associated with poor OS in HCC treated by radiofrequency-ablation (HR = 1.28, 95%CI: 1.10-1.48, P = 0.000), TACE (HR = 2.52, 95% CI: 1.64-3.86, P = 0.000) and mixed treatment (HR = 1.85, 95%  CI: 1.40-2.44, P = 0.000), respectively. In addition, high NLR was significantly correlated with the presence of vascular invasion (OR = 2.69, 95% CI: 2.01–3.59, P = 0.000), tumor multifocality (OR = 1.74, 95% CI: 1.30–2.34, P = 0.000) and higher incidence of AFP ≥ 400 ng/ml (OR = 1.46, 95% CI: 1.01–2.09, P = 0.04). CONCLUSION: Elevated NLR indicates a poor prognosis for patients with HCC. NLR may be a convenient, easily-obtained, low cost and reliable biomarker with prognostic potential for HCC.